Understanding Online Banking Acceptance By Jordanian Customers: The Effect Of Trust Perceptions - Al-Sharafi, Mohammed A.; Ruzaini, Abdullah Arshah; Alajmi, Qasim; Herzallah, Fadi (UTM Press, 2016)
Trust is essential for all online transactions adoption and usage including online banking. In this paper, online banking trust was addressed through empirical evidence from the survey conducted in Jordanian commercial banks. An extended Technology Acceptance Model (TAM) framework used in this study. Partial Least Squares (PLS) to analyze the data, which was composed of 198 questionnaires conducted with bank’s customers in Jordan. The results confirm that trust increases if users perceive online banking to be useful whereas perceived ease of use fails to predict Jordanians’ intention to accept and use online banking. The findings from this study are useful for policy makers, banking sectors and financial practitioners to enhance the use of online banking services among Jordanians.